2018
DOI: 10.2196/resprot.9087
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Implementing a Home-Based Couple Management Guide for Couples Where One Partner has Dementia (DemPower): Protocol for a Nonrandomized Feasibility Trial

Abstract: BackgroundThe increasing rate of dementia and high health and social care costs call for effective measures to improve public health and enhance the wellbeing of people living with dementia and their relational networks. Most postdiagnostic services focus on the condition and the person with dementia with limited attention to the caring spouse or partner. The key focus of the study is to develop a guide for couples where one partner has a diagnosis of dementia. This couple management guide is delivered in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A way of doing this might be to use the CARE intervention on emotional communication as described by Williams et al (). Further, Lasrado et al () suggested a home‐based couple management guide (DemPower) that focused on activities that can be done together as a tool to increasing the sense of togetherness. It is possible that couplehood and togetherness in situations where one partner has dementia may strengthen the sense of person‐centredness for both the person with dementia and the spouse.…”
Section: Discussionmentioning
confidence: 99%
“…A way of doing this might be to use the CARE intervention on emotional communication as described by Williams et al (). Further, Lasrado et al () suggested a home‐based couple management guide (DemPower) that focused on activities that can be done together as a tool to increasing the sense of togetherness. It is possible that couplehood and togetherness in situations where one partner has dementia may strengthen the sense of person‐centredness for both the person with dementia and the spouse.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed inclusion and exclusion criteria for recruitment are listed in Textbox 1 [ 19 ]. The participant characteristics were not limited to types of dementia, comorbidities, sexual orientation, age, profession, or social, cultural, or religious beliefs.…”
Section: Methodsmentioning
confidence: 99%
“…The outcomes of quality of life, self-efficacy, interconnectedness, and mutuality were measured using validated tools for both partners at baseline and postintervention. All outcome measures used in this study are listed in Table 2 [ 19 ]. The tools ranged from 1 to 15 items, with 3- to 5-point Likert scales and response options.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations